Efecto de la aplicación de ALGASOIL ® sobre el rendimiento y valor nutricional del kikuyo (Pennisetum clandestinum Hoechst. Ex Chiov.) en Palmira, Zarcero, Alajuela, Costa Rica - Aguilar-Rodríguez, Roberto Antonio (Instituto Tecnológico de Costa Rica, 2017)
Aguilar, R. 2017. Effects of the application of Algasoil® on the efficacy and nutritional value of the kikuyo (Pennisetum clandestinum Hoechst Ex Chiov.) In Palmira, Zarcero, Alajuela, Costa Rica. The present work was conducted with the objective of evaluating the effect of the commercial fertilizer Algasoil® on the production and nutritional value of kikuyo forage (Pennisetum clandestinum Hoechst, Ex Chiov.) and its economic feasibility in the dairy cattle production system in the El Encino farm. The “El Encino” farm is owned by the Blanco Porras family. The farm is located in Palmira, Zarcero, Alajuela, Costa Rica, located at 10 ° 12 '01.5 "north latitude and 84 ° 22' 57.4" west longitude, at a altitude of 1980 m. The farm receives an average annual precipitation of 2735 mm and has an average monthly temperature of 17.3 ° C and 80% relative humidity. In this project, four treatments were carried out: treatment 1 (farm management 113 kg of urea Ha-1); treatment 2 (farm management 113 kg of urea Ha-1 + 75 kg of Algasoil® Ha-1); treatment 3 (farm management 113 kg of urea Ha-1 + 50 kg of Algasoil® Ha-1) and treatment 4 (farm management 113 kg of urea Ha-1 + 25 kg of Algasoil® Ha-1). All treatments were applied by hand three days after each grazing cycle (1 day of grazing followed by 31 of rest). For the dry matter production, significant differences were found between treatments with Algasoil® and the control (3,427, 4,646, 4,486 and 4,179 kg MS Ha-1, for one through four treatments respectively). No significant differences in the value of the dry matter were found between treatments for any of the evaluated variables (ash 10.36%, ethereal extract 3.02%, FND 54%, FAD 28%, lignin 1.99% and PC 24.4%). Fertilization costs were higher for the control treatment as the application level of Algasoil® increased (costs were 29.907, 79.790, 63.149 and 46.528 colones Ha-1 respectively for treatments one through four).
Trabajo Final de Graduación (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2017.
Keywords: Producción lechera; Pastoreo; Materia seca; Factibilidad; Nutrición; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Agronomy